Parents’ beliefs in shaping family language planning: Narrative inquiry of Balti families living in Skardu - Shumaila Shafket Ali; Muhammad Issa (Journal of Language and Pragmatics Studies, 2026)
Although language planning, which is done at state level plays a pivotal role in deciding the fate of indigenous or heritage languages, family language planning, which is based on language beliefs, language practices, and language management within the home domain, has an equally crucial role to play in contributing towards heritage language maintenance or loss. Being a relatively new field of inquiry, this area needs to be investigated concerning the heritage language communities in Pakistan, which is home to almost 74 indigenous languages. Considering the relevance of FLP and the inclusion of 27 indigenous languages spoken in Pakistan in UNESCO’s list of endangered languages, the current study aims to undertake a narrative inquiry of six Balti couples, three living in a joint family while three living in a nuclear family system in Skardu. The data collection instruments include the life stories of these six Balti couples, followed by a series of interviews with them, along with the observations based on their use of language(s) with their children and other family members in the home domain. Despite some similarities in the Balti couples’ approach to and use of their mother tongue in the home domain, the findings of the study indicate significant differences in their FLP, which can be attributed to the differences in their family structure as well as other internal and external factors, like their language attitude, language ideology, subjective ethnolinguistic vitality, educational background, profession, the place of residence, etc. The findings of the study can empower the stakeholders, who may be directly or indirectly affected by the linguistic choices made in the home domain, and how these linguistic choices shape their beliefs about FLP. The study is an attempt to reinforce the importance of heritage language maintenance to arrest the loss of heritage languages and cultures.